Diagnosis and management of transient smartphone blindness: A literature review - Azzahra Afifah; Fara Syafira; Dini Dharmawidiarini (Faculty of Medicine, Universitas Islam Indonesia, 2023)
The development of smartphones worldwide has rapidly increased the number of smartphone users. Although smartphones have many benefits, prolonged use causes various visual disorders, of which transient smartphone blindness (TSB) is one of the most important concerns. This study aims to analyse the phenomenon of TSB and explore its etiology, pathophysiology, symptoms, and examination to determine the diagnosis and management. Transient smartphone blindness is a new physiologic phenomenon caused by exposure to a certain level of smartphone bright light and the body posture of the smartphone user. It leads to the use of monocular vision to stare at the smartphone. By exploring recent literature, this study found that patients with TSB experienced retinal photopigment bleaching, which decreased light sensitivity. Typically, the sensitivity returned physiologically after several minutes. Patients with this blindness showed several symptoms. For example, they perceived shapes, outlines, or figures during the blackout. The diagnosis of TSB should be primarily based on a detailed history of smartphone use, with the differential diagnosis based on circumstance or occurrence. This diagnosis is useful to distinguish it from transient ischemic attack (TIA). Transient smartphone blindness is a basic monocular transient loss that does not require therapy or drugs. However, it was found that the reassurance of patients’ condition and suggestions on smartphone use were sufficient for the intervention. With a limited scientific study of TSB, this review is the first to raise the discussion topic. It is expected to help physicians to diagnose TSB significantly. In addition, this study will enrich the literature, particularly on the scientific and clinical mechanisms of recognising TSB for clinical diagnosis and management.